2017
DOI: 10.3389/fonc.2017.00127
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Oncolytic Activity of CD133-Targeted Measles Virus: Receptor Extension or Chimerism with Vesicular Stomatitis Virus Are Most Effective

Abstract: Therapy resistance and tumor recurrence are often linked to a small refractory and highly tumorigenic subpopulation of neoplastic cells, known as cancer stem cells (CSCs). A putative marker of CSCs is CD133 (prominin-1). We have previously described a CD133-targeted oncolytic measles virus (MV-CD133) as a promising approach to specifically eliminate CD133-positive tumor cells. Selectivity was introduced at the level of cell entry by an engineered MV hemagglutinin (H). The H protein was blinded for its native r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…More recently, a similar approach was used to retarget replication-competent chimeric VSV-FH to cancer cells, especially ovarian cancer cells, expressing HER-2/neu receptor [42]. In another study, VSV encoding CD133-targeted MV-H and the MV-F was generated and successfully targeted cancer cells expressing a putative marker of cancer stem cells CD133 in a subcutaneous hepatocellular carcinoma (HCC) xenograft model [43]. As MV also infects nectin4-positive airway epithelial cells, a modified VSV-FH recombinant was generated with H mutations that disrupts binding to nectin4, which were expected to improve the virus oncoselectivity by limiting its binding only to CD46.…”
Section: Attenuation Of Vsv Through Disruption Of Normal Gene Ordermentioning
confidence: 99%
“…More recently, a similar approach was used to retarget replication-competent chimeric VSV-FH to cancer cells, especially ovarian cancer cells, expressing HER-2/neu receptor [42]. In another study, VSV encoding CD133-targeted MV-H and the MV-F was generated and successfully targeted cancer cells expressing a putative marker of cancer stem cells CD133 in a subcutaneous hepatocellular carcinoma (HCC) xenograft model [43]. As MV also infects nectin4-positive airway epithelial cells, a modified VSV-FH recombinant was generated with H mutations that disrupts binding to nectin4, which were expected to improve the virus oncoselectivity by limiting its binding only to CD46.…”
Section: Attenuation Of Vsv Through Disruption Of Normal Gene Ordermentioning
confidence: 99%
“…Second, they emphasize the importance of the tumor microenvironment on tumor progression, and validate the tumor stroma as a target for oncolytic virotherapies in general, and oncolytic MVs in particular. Prior studies have characterized fully retargeted MVs directed against multiple receptors, such as the epithelial receptors Her-2/ neu and EpCAM [46], or against CD46 and CD133 [47], among other retargeted oncolytic MVs. Although these strategies enhance and potentiate tumor targeting, they do not address the important question of stromal targeting by MV vectors.…”
Section: Discussionmentioning
confidence: 99%
“…For the association of CD133 with CRC treatment, several studies have reported that CD133-positive CRC might be resistant to chemotherapy or chemoradiotherapy (41)(42)(43). Moreover, CD133-targeted oncolytic measles virus has been shown to specifically eliminate CD133-positive tumor cells (glioblastoma and hepatocellular carcinoma) in a murine model (44); however, fatal neurotoxicity was developed in this model. Based on these studies, DCLK1 seems to be the most promising target for CRC treatment, at present.…”
Section: Discussionmentioning
confidence: 99%